Strategies for engineering oncolytic viruses to enhance cancer immunotherapy - Yin, Ziyang (Steve); Wang, Zhengfeng (Frontiers in Pharmacology, 2024)
Non-small cell lung cancer (NSCLC) is the predominant form of lung cancer and is characterized by rapid metastasis and high mortality, presenting a challenge for early-stage treatment modalities. The heterogeneity of NSCLC's tumor microenvironment (TME) significantly influences the efficacy of anti-PD-1 immune checkpoint inhibitors (ICIs) therapy, leading to varied patient responses. This review characterized different strains of oncolytic viruses in NSCLC and the different gene edits in pre-existing oncolytic viruses. This study also aimed to provide strategies to enhance anti-PD-1 therapy in NSCLC by engineering oncolytic viruses (OVs). This study offers insights into the genomic adaptations necessary for OVs targeting NSCLC, identify genetic determinants of anti-PD-1 response variability, and propose genomic edits to bolster therapy effectiveness. The primary goal of this study is to present a theoretically designed OV with a detailed genomic framework capable of enhancing the response to anti-PD-1 therapy, thereby advancing the field of cancer immunotherapy.